2015
DOI: 10.1245/s10434-015-4787-6
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Success Rate of Repeat Sentinel Node Biopsy in Recurrent Breast Cancer

Abstract: Repeat SNB is a technically feasible procedure for axillary staging in recurrent breast cancer patients. Previous radiotherapy appears to be associated with failure of SN identification. Injection with a larger amount of tracer (>180 MBq) leads to a higher identification rate; subareolar injection and a 2-day LM protocol after previous BCS appear to be less adequate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…As published before, injection with a larger amount of tracer leads to a higher identification rate. 32 In this study, patients with regional recurrence had a significantly lower amount of tracer injected. Injection of a higher tracer dose might have led to identification of repeat sentinel lymph nodes in additional basins.…”
Section: Discussionmentioning
confidence: 63%
“…As published before, injection with a larger amount of tracer leads to a higher identification rate. 32 In this study, patients with regional recurrence had a significantly lower amount of tracer injected. Injection of a higher tracer dose might have led to identification of repeat sentinel lymph nodes in additional basins.…”
Section: Discussionmentioning
confidence: 63%
“…The SNARB study (Sentinel Node and Recurrent Breast Cancer) by Vugts et al, which is a multicenter study on the feasibility and clinical usefulness of the repeat SLNB, showed that the limited SLN visualization may be caused by previous radiotherapeutic treatment. In addition, it was advised to inject a larger amount of radioactive dye and a 1-day protocol for lymphoscintigraphy was proposed instead of the current 2-day protocol to increase the visualization rate [26]. Studies also show that the success rate of the SLN procedure increases when both the lymphoscintigraphy and Patent Blue methods are used and when a larger amount of radioactive dye is injected [23,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…The dual mapping technique with both 99m Tc and blue dye was used for the rSLNB procedure. Technical specifications and determinants of successful rSLNB have been reported in detail elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…In patients with an unsuccessful rSLNB, a sentinel node could not be visualized and/or harvested because of an unsuccessful procedure. In these patients, injection of a second dose of radiolabelled tracer was allowed, or the physician could act in accordance with the local protocol. There was no requirement to perform an ALND in patients with an unsuccessful rSLNB.…”
Section: Methodsmentioning
confidence: 99%